Inovasi Merdeka Belajar: Pelatihan Penerapan Microlearning dan Microcontent untuk Pembelajaran Geografi Berdiferensiasi - Putra, Alfyananda Kurnia; Khalidy, Diky Al; Handoyo, Budi; Soekamto, Hadi; Kristanti, Queentasya Vanti Dian; Kholifah, Evalia Nurul; Putri, Denok Pangestudika Arum; Ayu, Yasmin Fajar Putri (Universitas Mataram, 2024)
The development of technology has led to a transformation in the field of learning into a smart learning environment. However, the unpreparedness of institutions, such as facilities and infrastructure, as well as the lack of digital pedagogy among teachers, such as low technology literacy, a lack of creativity, and confidence in implementing digital-based learning, poses significant challenges. The solution to these problems involves conducting training and utilizing microlearning and microcontent for differentiated learning within the independent curriculum through workshop activities. The method of community service involves the active participation of partners, namely the Geography Teachers' Association of Batu City, in workshop activities. The purpose of this community service is to train in the application of microlearning and microcontent in differentiated Geography learning within the Independent Curriculum. In its evaluation, the workshop activities have had a positive impact on the participants, received support from various parties, and there is follow-up to ensure that the activities are carried out continuously.